Pengaruh Ekstrak Buah Apel (Malus Sylvestris) Terhadap Perubahan Warna Gigi Dalam Proses Bleaching (Pemutihan Gigi) - Retno Satria; Rosa Amalia (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2007)
Apple consist of some chemical compound like ellagic acid and quinon. Apple tissue also has peroxidase that can be change into hydrogen peroxide with to help catalase. Hydrogen peroxide is on chemical compound that usually used for tooth whitening (bleaching). Ellagic acid also can be used for tooth whitening with the similiar chemical reaction of hydrogen peroxide. This research is to know do apple extract (Malus Sylvestris) have eﬂect to the degree of tooth colour changing of bleaching process.The design of this research is laboratory experimental an in vitro with 15 non vital tooth as sample. This research use apple extract 100% (test group), hydrogen peroxide 10% (positive control group), and aquades (negative control group). Those 3 materials were put into 3 different glasses with 30 ml volume and each 5 tooth were inserted into each glass. The tooth lighted with spectrophotometer before the soaked. Then tooth were soaked for 96 hours (4 days). After the soaked, the tooth lighted again for counting the degree of tooth colour change based on the result from the spectrophotometer.The result of the statistic test use paired t-test shows that there was signiﬁcant differences in tooth colour change in three of the test. Value from apple extract 100%p=0, 02, hydrogen peroxide I 0%p=0, 00 and aquades p=0, 03 (p0, 05). Based on the statistic result, can concluded that apel apple extract can the degree of tooth colour change or changing oftooth colour to be whiter (brighter), after soaked for 96 hours (4 days). Acid component in the apple use in high concentration and long time can damage tooth email and tooth porosity.